Storage of blood and the mean corpuscular volume. - Lawrence, A C (1975)
The mean corpuscular volume (MCV) of blood after storage for up to 24 days under various temperature conditions in ethylene diamine tetracetic acid, acid citrate dextrose, citrate phosphate dextrose, and Alsever's solution was measured using the Coulter S. Storage of blood overnight at 23 degrees centigrade increased the MCV, while there was no significant change after similar storage at 4 degrees C. Storage of blood for 23 days at 4 degrees C for 24 days. Similar results were found with all anticoagulants tested. The precision of the MCV varied on storage with different anticoagulants.